C'1 ESTERASE EFFECT ON ACTIVITY AND PHYSICOCHEMICAL PROPERTIES OF THE FOURTH COMPONENT OF COMPLEMENT - Müller-Eberhard, Hans J. (The Rockefeller University Press, 1965)
Highly purified C'1 esterase of human serum is capable of inactivating isolated fourth component of human complement (β(1E)-globulin). Inactivation is accompanied by changes in electrophoretic and ultracentrifugal properties of β(1E)-globulin. If non-sensitized sheep erythrocytes are present during the action of C'1 esterase on β(1E)-globulin, a complex is formed consisting of cells and cytolytically active fourth component (EC'4). Thus, inactivation of β(1E)-globulin by C'1 esterase appears to be preceded by a state of activation enabling β(1E)-molecules to combine with cell membrane receptors. Acceptor groups appear to be present also in 7S γ-globulin and in β(1E)-globulin itself, since C'1 esterase can induce the formation of β-β and of β(1E)-7S γ-globulin complexes.